2012
DOI: 10.1159/000341976
|View full text |Cite
|
Sign up to set email alerts
|

Copper, Zinc, and Cu/Zn Ratio in Transitional Cell Carcinoma of the Bladder

Abstract: Introduction: Many epidemiological and experimental studies report a strong role of chemical carcinogens in the etiology of bladder cancer. However, involvement of trace elements in the tumorigenesis of transitional cell carcinoma of the bladder has been poorly investigated. The aim of this study was to examine the relationship between zinc, copper and bladder cancer. Materials and Methods: Zinc and copper concentration and Cu/Zn ratio in two 36-sample series of bladder cancer tissue and sera from patients wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
28
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 40 publications
(32 citation statements)
references
References 46 publications
3
28
0
1
Order By: Relevance
“…We observed significant elevations of Cu/Zn ratio in total cases compared to the control group (Table 1). This finding is in agreement with reports of the most previous studies suggesting markedly elevated serum Cu/Zn ratio in cancers, such as CRC, bladder, prostate, breast, thyroid, and liver cancer [8,11,19,38].…”
Section: Resultssupporting
confidence: 93%
See 2 more Smart Citations
“…We observed significant elevations of Cu/Zn ratio in total cases compared to the control group (Table 1). This finding is in agreement with reports of the most previous studies suggesting markedly elevated serum Cu/Zn ratio in cancers, such as CRC, bladder, prostate, breast, thyroid, and liver cancer [8,11,19,38].…”
Section: Resultssupporting
confidence: 93%
“…Exposure to reactive oxygen species (ROS) can lead to direct DNA damage, mutation, and carcinogenesis [6,7]. Previous studies have reported alterations in the concentrations of serum or neoplastic tissue trace elements in various carcinomas including breast, bladder, gastric, gallbladder, and lung cancers [1,[8][9][10][11][12].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…There is an emerging understanding of toxic and carcinogenic effects of certain heavy metals and trace elements in both animals and humans [1][2][3][4][5][6][7]. Chromium (Cr) is a known human carcinogen and has been hypothesized as a cause of several cancers, including leukaemia and neoplasms of lung, nose and nasal sinuses [8][9][10].…”
Section: Introductionmentioning
confidence: 99%
“…Many chemicals, including heavy metals and trace elements, have been shown to be carcinogens for bladder cancer [10][11][12]. Experimental studies have demonstrated that cadmium can induce both benign and malignant tumour formation at various sites including the urinary tract [13][14][15][16].…”
Section: Introductionmentioning
confidence: 99%